THE STUDY OF THE OSMOTIC ACTIVITY OF OPHTALMIC GELS - M. N. Anurova; E. O. Bakhrushina; I. V. Lapik; A. S. Shitova; I. I. Krasnyuk (Разработка и регистрация лекарственных средств, 2019)
Studies of the osmotic activity of emoxypine and dalargine ophthalmic experimental gels samples based on various polymers and also studies of some marketed in Russia ophthalmic gels are presented in the article. Selection of the most promising for further study emoxypine and dalargine experimental gel compositions was based on the comparative study of Vidisic®, Solcoseryl®, Corneregel®, Oftagel® ophthalmic gels as well as 0,9% sodium chloride solution used as the standard of osmolality. Optimal values of osmotic activity have an experimental sample of an emoxypine ophthalmic gel containing Natrosol™ 250HHX at a concentration of 1%, as well as Oftagel® and Solcoseryl® gels.